CHALLENGES IN WOOD DENSIFICATION: PROCESSING AND PROPERTIES - Navi, Parviz (Innovation in Woodworking Industry and Engineering design, 2013)
Wood can be densified and moulded through the combined effects of temperature, humidity and mechanical forces. These processes so called THM treatments. Depending to the processing parameters the physical and mechanical properties of wood can improve considerably. Although, the principles of densification of small wood elements are well known, challenges are faced in scaling-up stage and on the shape memory. The aim of this paper is to explain the origin of the shape memory and the effect of combined Thermo-Hydro-Mechanical on the fixation of compression. The process of densification can be implemented in an open system, a semi-open system or a closed system. In an open system part of the boundary conditions is open to climate and control of moisture content as well temperature of the elements during densification is not possible. But in a closed system all these parameters are under control. Although, densification of wood in an open system improves the mechanical and durability of wood, but the compression-set is not stable. Post-processing THM treatments have shown to constitute an effective means of eliminating the set-recovery. We have shown that hydrolysis of hemicelluloses during THM post treatment plays an important role in the elimination of shape memory through the dissipation of the stresses (relaxation) stored in the microfibrils and the matrix during densification. We have shown that for a total elimination of shape memory it is necessary for the lignin to be in its rubbery state during the THM treatment.